2021
DOI: 10.1186/s13046-021-01932-8
|View full text |Cite|
|
Sign up to set email alerts
|

ALG3 contributes to stemness and radioresistance through regulating glycosylation of TGF-β receptor II in breast cancer

Abstract: Background Radiotherapy is a conventional and effective local treatment for breast cancer. However, residual or recurrent tumors appears frequently because of radioresistance. Novel predictive marker and the potential therapeutic targets of breast cancer radioresistance needs to be investigated. Methods In this study, we screened all 10 asparagine-linked glycosylation (ALG) members in breast cancer patients’ samples by RT-PCR. Cell viability after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 87 publications
0
45
0
Order By: Relevance
“…Increased expression of ALG3 was observed in HNSCC cell line ( 26 ). Moreover, ALG3 as a class of glycosyltransferases promotes the proliferation and radiosensitivity of cancer cells and is related with poor prognosis and lymph node metastasis ( 27 , 28 ). CHPF2 acts as an oncogene that is up-regulated in cancers to exert its positive role in cell proliferation and metastasis, including breast cancer, hepatocellular carcinoma, lung adenocarcinoma, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Increased expression of ALG3 was observed in HNSCC cell line ( 26 ). Moreover, ALG3 as a class of glycosyltransferases promotes the proliferation and radiosensitivity of cancer cells and is related with poor prognosis and lymph node metastasis ( 27 , 28 ). CHPF2 acts as an oncogene that is up-regulated in cancers to exert its positive role in cell proliferation and metastasis, including breast cancer, hepatocellular carcinoma, lung adenocarcinoma, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, TGFβ, CXCR4, and αvβ3 integrin are key mediators of breast cancer metastasis to bone (Table 2) [93][94][95][96]. Antagonists of these proteins are under investigation in preclinical models of metastatic breast cancer, showing accumulating positive data [97][98][99][100][101][102][103][104][105][106][107][108]. Assessment of their safety and efficacy in phase I clinical trials is expected.…”
Section: Drug Classmentioning
confidence: 99%
“…A study by Sun et al further looked into the association between TGF-β, CSC enrichment, and radioresistance. Sun et al demonstrated that following initial radiotherapy, breast cancer patients who demonstrated radioresistance and recurrence within 5 years of their initial therapy were found to have increased expression of ALG3 (Alpha-1,3-Mannosyltransferase) [73]. These findings were correlated with breast cancer cell lines where basal-like and HER-2+ breast cancer lines demonstrated increased levels of radioresistance and ALG3 expression.…”
Section: Tgf-β As a Therapeutic Target To Inhibit Tnbc And Its Csc Populationmentioning
confidence: 99%
“…This co-immunoprecipitation was not observed in ALG3 knockout cell lines. A TGFβR2 inhibitor (LY2109761) was then used to inhibit ALG2 overexpressing breast cancer cell lines which induced apoptosis post-radiotherapy and diminished tumorsphere formation as well as CD44+/CD24-CSCs [73].…”
Section: Tgf-β As a Therapeutic Target To Inhibit Tnbc And Its Csc Populationmentioning
confidence: 99%